(untitled) (Journal of the College of Basic Education, 2022)
The effect of orange peel powder on lipids profile in normal and oxidative stress albino mice was studied. Fifty-four albino mice were randomly divided into six groups (nine animals in each group). The first group was considered as control, the second, third and fourth groups were supplied with pellets containing 0.1, 0.2 and 0.4% orange peel powder for 21 days. The fifth group was subjected to H2O2 (0.15%) in drinking water for ten days. The last group was subjected to H2O2 (0.15%) and supplied with pellets containing the optimum concentration of orange peel powder for 14 days. The results showed that there was a significant (P<0.05) decrease in lipid profile parameters, except HDL-C concentration which increased significantly (P<0.05) in the three groups treated with orange peel powder and orange peel powder + hydrogen peroxide compared with stress animals. It is concluded that orange peel powder decreases serum TC, TG, LDL-C, VLDL-C levels and atherosclerosis index in the experimental animals. Therefore, the orange peel powder is recommended to prevent the development of hypercholesterolemic and coronary heart diseases. Key words: orange peel, oxidative stress, cholesterol, triglycerides, high-density lipoprotein, low-density lipoprotein